2015
DOI: 10.1136/bmjopen-2015-007618
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in ovarian cancer: a systematic review and meta-analysis of prevalence rates

Abstract: ObjectivesTo systematically review the literature pertaining to the prevalence of depression and anxiety in patients with ovarian cancer as a function of treatment stage.DesignSystematic review and meta-analysis.Participants3623 patients with ovarian cancer from primary research investigations.Primary outcome measureThe prevalence of depression and anxiety in patients with ovarian cancer as a function of treatment stage.ResultsWe identified 24 full journal articles that met the inclusion criteria for entry int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
127
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(139 citation statements)
references
References 44 publications
2
127
2
8
Order By: Relevance
“…Compared with young counterparts, elderly patients are more likely to have an advanced stage at diagnosis . Also, the previous study confirmed that the prevalence of mental disorder in ovarian cancer had association with cancer stage . Other studies have also reported that performance status, such as ECOG, indicates the biologic age was more relevant to prognosis than the actual age .…”
Section: Discussionsupporting
confidence: 54%
“…Compared with young counterparts, elderly patients are more likely to have an advanced stage at diagnosis . Also, the previous study confirmed that the prevalence of mental disorder in ovarian cancer had association with cancer stage . Other studies have also reported that performance status, such as ECOG, indicates the biologic age was more relevant to prognosis than the actual age .…”
Section: Discussionsupporting
confidence: 54%
“…It also reemphasizes the need for true baseline preoperative HRQOL measures in all oncology trials where surgery is a component of care. A systematic review of longitudinal anxiety in ovarian cancer patients, published in 20 1 5, 20 featured 7 studies with labeled “pretreatment” baseline anxiety levels, only 1 of which actually reported preoperative baseline anxiety, and consisted of 27 patients total. 21 …”
Section: Commentmentioning
confidence: 99%
“…Between 30% and 42% of women with gynecological cancer report moderate to severe anxiety [2,3] and up to one third report moderate to severe levels of depressive symptoms [2, 4-6]. Post-treatment studies indicate that between 22% and 27% report elevated anxiety and between 6% and 13% report elevated depression [3,7]. …”
mentioning
confidence: 99%